Rekonstruksi Hakikat Pendidikan Kristen sebagai Proses Formasi Karakter dan Spiritualitas dalam Konteks Era Digital - Talizaro Tafonao; Rolina Anggereany Ester Kaunang; Lukas Lukas (P3M STT Kristus Alfa Omega, 2026)
Amid rapid digital transformation, Christian education encounters a fundamental yet often overlooked challenge: the disruption of faith internalization processes. Values that are taught no longer automatically translate into students’ character and spirituality, resulting in a gap between theological understanding and everyday practice. This study aims to examine the nature of Christian education as a process of character and spiritual formation in the digital era, identify its key challenges, and propose a relevant and integrative pedagogical framework. This research adopts a qualitative approach using a literature review method, employing descriptive-analytical techniques to examine various scholarly sources. The findings indicate that Christian education should be understood as a holistic formation process encompassing stages of internalization, habituation, and transformation. This process must be supported by reflective pedagogy, authentic role modeling, and contextual engagement with digital technology. Furthermore, the study reveals that digital disruption can be transformed into a constructive opportunity when meaningfully integrated into the learning process. The novelty of this research lies in the development of an integrative model that bridges theological, pedagogical, and technological dimensions, while emphasizing collaboration among schools, families, and churches. Therefore, Christian education needs to be contextually reconstructed to remain relevant and effective in fostering character and spiritual formation in the digital age.